Re-engineering as the Process of Business Adaptations - Novikov, Vladimir S.; Pykhtin, Aleksey I.; Gureva, Maria A.; Sozinova, Anastasiya A.; Prokhorova, Maria P. (International Journal of Economics and Financial Issues, 2016)
Reengineering - is primarily a result of information technology. Due to the method of reengineering, we can consider the activities of enterprises, highlighting their function. Every company or organization has a plan. About two hundred years ago, it was shown that by sharing the work, the person focuses on one thing, and it performs better. Guided by this discovery of Adam Smith, the people for a long time applied the principle of division of labour. Currently, the production cannot be called effective. Highly specialized work superseded the multistage division of labour, which requires the coordination of all phases of the production process. Economic viability and competitiveness of the companies must be based on the adoption of new models of organizations. One of the conditions for success in reengineering and its implementation is considered to be the drafting of another, already the updated business process with the implementation of a large arsenal of techniques. To perform reengineering is assigned a person who is the project leader (the company of senior management). Then we formed a team, which includes specialists and experts. Create Committee monitors the implementation of engineering strategy and to monitor the implementation of the project. Keywords: business, reengineering, information technology, innovation management JEL Classifications: D24, Ðœ1, Ðž31